2007
DOI: 10.1111/j.1538-7836.2007.02295.x
|View full text |Cite
|
Sign up to set email alerts
|

IgG classification of anti‐PF4/heparin antibodies to identify patients with heparin‐induced thrombocytopenia during mechanical circulatory support

Abstract: IgG classification of anti-PF4/heparin antibodies to identify patients with heparin-induced thrombocytopenia during mechanical circulatory support. See also Warkentin TE. PF4-dependent immunoassays and inferential detection of HIT antibodies. This issue, pp 232-4.Summary. Commercial immunoassays frequently detect anti-PF4/heparin antibodies during mechanical circulatory support (MCS), but only a small minority of patients develops heparininduced thrombocytopenia (HIT). Whereas platelet functional tests can dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 28 publications
0
31
0
Order By: Relevance
“…Several groups have suggested that the magnitude of a positive ELISA is clinically relevant, 35,[38][39][40][41] and concerning the ID-H/PF4-PaGIA, we had already demonstrated the clinical utility of this approach. 3,22 In the present study, ROC analysis confirms a cut-off titer of 4 or over 3,22 as providing the best compromise between sensitivity and specificity, and shows that titers of 32 or over have a PPV of 100% for the presence of in vitro platelet-activating HIT antibodies.…”
Section: Discussionmentioning
confidence: 67%
“…Several groups have suggested that the magnitude of a positive ELISA is clinically relevant, 35,[38][39][40][41] and concerning the ID-H/PF4-PaGIA, we had already demonstrated the clinical utility of this approach. 3,22 In the present study, ROC analysis confirms a cut-off titer of 4 or over 3,22 as providing the best compromise between sensitivity and specificity, and shows that titers of 32 or over have a PPV of 100% for the presence of in vitro platelet-activating HIT antibodies.…”
Section: Discussionmentioning
confidence: 67%
“…Most commercially available anti‐PF4/heparin antibody ELISA kits detect all three isotypes, whereas antibodies capable of activating platelets are typically of the IgG isotype . Lack of isotype specificity may reduce the overall specificity of a positive test result , although Selleng et al . noted no association between preoperative or postoperative IgG antibodies and thromboembolism, but rather an association between IgM antibodies and non‐thrombotic complications after cardiac surgery.…”
Section: Discussionmentioning
confidence: 99%
“…on April 30, 2019. by guest www.bloodjournal.org From unlikely to be present. 17,18 This strategy is feasible in countries where functional HIT tests are available from a network of trained laboratories, providing assays in a turnaround time and of sufficient quality that clinical decisions may be based on the test result. (Potential alternative approaches are given in Table 1.…”
Section: Heart Transplantation In Subacute Hit Patients 4025mentioning
confidence: 99%